'Bad influence' and 'willful subjects': the gender politics of The Life of Poetry. Issue 7 (9th August 2018) - Kennedy-Epstein, Rowena
ABSTRACT: In The Life of Poetry, Muriel Rukeyser writes that the resistance to poetry comes not just from its being viewed as 'intellectual and obscure and confused' but also because it is considered 'sexually suspect'. Bringing together these questions about gender and genre from the outset, one of Rukeyser's central projects is to unveil and confront the gender norms of Cold War containment culture – norms that positioned the queer body and communist body as dangerous, the male body as antagonistic to the female body, and that underscored the policing of literary and disciplinary categories. The gender politics of the text become fully legible when read alongside 'The Usable Truth' – the lectures delivered through the 1940s that would become the 1949 book – and in the context of her unpublished essay about women poets, Many Keys – commissioned but rejected by The Nation in 1957 – that expands on ideas in The Life of Poetry . While Rukeyser was deeply engaged in thinking about the place of the woman writer, this essay considers the repressive conditions that contributed to the absence of an overt gender analysis in the final version of The Life of Poetry, while exploring Rukeyser's wilful persistence in pursing radical textual and sexual theories of multiplicity.